Religious Energizer and Librarians’ Performance - Fatmawati, Riya; Laugu, Nurdin; Sha’adah, Nurush (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2024)
Religious energizer is a term that is frequently used to define an individual who serves as a facilitator in everyday life, including work, based on their knowledge and religious teaching. In the librarians’ circumstances, the religious energizer behavior can be observed through their attitudes at work. These behaviors arise from their experience and religious knowledge, which then disseminate to their work circumstances and relatives. This research aims to determine the religious activities carried out by librarians as religious energizers to support their performance at UIN Imam Bonjol Padang. This research is descriptive with a qualitative approach, using interviews, observations, and documentation methods to get information and data. The object of this research is the UIN Imam Bonjol Padang library, while the subjects are three librarians of UIN Imam Bonjol as informants. The samples are generated based on a purposive sampling technique with particular criteria such as respect for librarians in work. After getting information and data, the author analyzed the data using triangulation, considering several steps such as data reduction, data display, and drawing conclusions. The finding revealed that three main activities reflect religious energizers performed by librarians at the State Islamic University of Imam Bonjol, Padang, such as 1) participation in religious practices, 2) sharing information, and 3) morning meetings. These activities bring librarians positive energy and vitality, conceivably upgrading their mental and emotional stability at work. Therefore, it is evident that religious energizers can improve the performance of librarians at the UIN Imam Bonjol, Padang library.